Pengaruh Literasi Keuangan, Kemudahan, Keamanan, Dan Gaya Hidup Terhadap Penggunaan Sistem Digital Qris Pada Mahasiswa STIE Bina Karya - Yulia Amanda; Kelvin Adfentri Samosir; Bobby Hartanto; Willy Cahyadi (CV. ITTC INDONESIA, 2026)
The development of financial technology has transformed payment systems from cash-based transactions to digital payments. One of the innovations introduced in Indonesia is the Quick Response Code Indonesian Standard (QRIS), which offers convenience, speed, and security in conducting transactions. Although the use of QRIS continues to increase, its adoption among university students is still influenced by several factors, including financial literacy, ease of use, security, and lifestyle. This study aims to analyze the influence of financial literacy, ease of use, security, and lifestyle on the use of the QRIS digital payment system among students of STIE Bina Karya Tebing Tinggi. This study employed a quantitative method with an explanatory research approach. The population consisted of 212 active students, while 68 respondents were selected using the Slovin formula. Primary data were collected through questionnaires using a Likert scale. Data were analyzed using SmartPLS 3.0 through validity testing, reliability testing, outer model evaluation, inner model evaluation, and hypothesis testing. The results indicate that financial literacy and ease of use do not have a significant effect on QRIS usage. In contrast, security and lifestyle have a significant effect on QRIS usage among students. Furthermore, financial literacy, ease of use, security, and lifestyle collectively provide a strong contribution in explaining QRIS usage behavior. This study concludes that security and lifestyle are the main factors influencing QRIS usage among students of STIE Bina Karya Tebing Tinggi. The findings provide implications for the development of safer digital payment systems and the improvement of financial literacy to encourage QRIS adoption among university students.